2020
DOI: 10.19128/turje.613091
|View full text |Cite
|
Sign up to set email alerts
|

Children’s science learning outside school: Parental support

Abstract: This study examined (a) the availability of basic science materials in children"s home environment, (b) the frequency of parents" involvement in informal science activities with their children, (c) the level of opportunities parents offered their children for learning basic science subjects, and (d) the effect of grade level on parental support for children"s science learning. In this cross-sectional survey study, data were collected from 735 parents in a city in the north region of Turkey. Results revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…The research findings point out that students' perceived emotional support in selected countries had a positive influence on science achievement. This finding parallel to the available literature, which indicates that students' perceived parental support impact their academic scores positively (Chen, 2008;Çobanoğlu and Yurttaş-Kumlu, 2020;Eberbach and Crowley, 2017;Flynn et al, 2018). This means that parental support plays a critical and determinant role in terms of promoting and strengthening their children's school life and improving academic success.…”
Section: Discussion Conclusion Limitations and Recommedationssupporting
confidence: 81%
See 1 more Smart Citation
“…The research findings point out that students' perceived emotional support in selected countries had a positive influence on science achievement. This finding parallel to the available literature, which indicates that students' perceived parental support impact their academic scores positively (Chen, 2008;Çobanoğlu and Yurttaş-Kumlu, 2020;Eberbach and Crowley, 2017;Flynn et al, 2018). This means that parental support plays a critical and determinant role in terms of promoting and strengthening their children's school life and improving academic success.…”
Section: Discussion Conclusion Limitations and Recommedationssupporting
confidence: 81%
“…Additionally, Hill and Taylor (2004) have underlined the gains to their children's social, emotional, and academic learning on educational support of parents at home and at school settings. Moreover, Çobanoğlu and Yurttaş-Kumlu (2020) have stated that mostly the parents had tendency to support their children's learning in the area of basic physical needs such as health, security, and nutrition than cognitive and emotional needs in the north region of Turkey. © 2022, Journal of Learning and Teaching in Digital Age, 7(2), 127-140…”
Section: Perceived Parental Support For Learningmentioning
confidence: 99%
“…In the research literature, a relatively large number of environmental education studies, which examine connections with nature, originate from Turkey, where the environmental education of 4th-8th-grade students in more informal pedagogical arenas has enjoyed great national attention since 1999 (Aydede-Yalçın, 2016). This focus has increased interest in environmental education as a research topic in education science and pedagogy in Turkey (Genc et al, 2018;Çobanoğlu and Kumlu, 2020).…”
Section: General Overview Of the Fieldmentioning
confidence: 99%
“…Internet connection is also a vital measure of home resources that help to create a conducive environment of learning for children (Visser et al, 2015;Gelmez-Burakgazi & Yildirim, 2014). A study among 735 Turkish parents revealed that most children did not have basic science materials at home (Cobanuglu & Yurttas-Kumlu, 2020). Parental support for children's science learning was examined across three different grade levels including preschool, elementary school and middle school grades in Cobanuglu and Yurttas-Kumlu (2020) had access to science-related computer applications at home unlike preschool (36.5%) and elementary school (41.3%) children (Cobanuglu & Yurttas-Kumlu, 2020).…”
Section: Student Use Of Internet For Schoolworkmentioning
confidence: 99%